Changes in subtypes of overt thyrotoxicosis and hypothyroidism following iodine fortification. (10th September 2019) - Petersen, Mads; Bülow Pedersen, Inge; Knudsen, Nils; Andersen, Stig; Jørgensen, Torben; Perrild, Hans; Ovesen, Lars; Banke Rasmussen, Lone; Thuesen, Betina H.; Carlé, Allan
Abstract: Objective: To investigate the impact of mandatory iodine fortification (IF) on the incidence of nosological subtypes of overt thyrotoxicosis and hypothyroidism. Design: We identified and scrutinized all possible new cases of overt thyrotoxicosis and hypothyroidism in an open cohort in Northern Jutland (n = 309 434; 1 January 1997) during the years 2014‐2016. Individual medical history was evaluated to verify and detail the incidence of overt thyroid dysfunction and for classification into nosological subtypes. A number of cases were excluded during final verification due to spontaneous normalization of thyroid function, as they had no medical history suggesting a known condition, which could transiently affect thyroid function (subacute/silent thyroiditis, PPTD and iatrogenic thyroid dysfunction). An identical survey was conducted in 1997‐2000 prior to mandatory IF of salt (13 µg/g) that was in effect from year 2001. Results: The standardized incidence rate (SIR) of verified overt thyrotoxicosis decreased markedly from 97.5/100 000/year in 1997‐2000 to 48.8 in 2014‐2016 (SIRR: 0.50 [95% CI: 0.45‐0.56]). This was due to a distinct decrease in the SIR of multinodular toxic goitre (SIRR: 0.18 [0.15‐0.23]), solitary toxic adenoma (SIRR: 0.26 [0.16‐0.43]) and to a lesser degree Graves' disease (SIRR: 0.67 [0.56‐0.79]). SIR for overt hypothyroidism was unaltered by 2014‐2016 (SIRR: 1.03 [0.87‐1.22]). However, age distribution shifted with more young and fewer elderly cases of verified overt hypothyroidism. Conclusion: Mandatory IF caused a substantial reduction in SIR of verified overt thyrotoxicosis (especially of nodular origin) while avoiding an increase in SIR of verified overt hypothyroidism.